Internato de Medicina preventiva e social: a formação médica no Amazonas para o trabalho no Sistema Único de Saúde brasileiro (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2018)
Internship of preventive and social Medicine: the medical education in the Amazonas state for the work in Brazilian Unified National Health System